TIGAR deficiency induces caspase-1-dependent trophoblasts pyroptosis through NLRP3-ASC inflammasome - Guo, Junjun; Zhou, Meijuan; Zhao, Man; Li, Shuxian; Fang, Zhenya; Li, Anna; Zhang, Meihua (Frontiers in Immunology, 2023)
Introduction Gestational diabetes mellitus (GDM), a common complication of pregnancy, is risky for both mother and fetus. Previous studies about TP53-induced glycolysis and apoptosis regulator (TIGAR) focused on the occurrence and development of cancer, cardiovascular disease, and neurological disease, however, it is still unclear whether TIGAR plays a regulatory role in gestational diabetes mellitus (GDM). Methods Utilizing HG exposure, we explored the role of TIGAR in oxidative stress limitation, excessive inflammatory toxicity defense, and pyroptosis prevention. Results TIGAR was up-regulated in vivo and in vitro under HG condition, and loss of TIGAR increased ROS in trophoblast cells which drove a phenotypic switch and hindered the capacity of migration, invasion, and tube formation. This switch depended on the increased activation of NLRP3-ASC-caspase-1 signaling, which caused a distinctive characteristic of pyroptosis, and these findings could finally be reverted by antioxidant treatment (NAC) and receptor block (MCC950). Collectively, trophoblast pyroptosis is an upstream event of TIGAR deficiency-induced inflammation, which is promoted by ROS accumulation through NLRP3-ASC inflammasome. Conclusion Taken together, our results uncovered that, as the upstream event of TIGAR deficiency-induced inflammation, pyroptosis is stimulated by ROS accumulation through NLRP3-ASC inflammasome.